2016
DOI: 10.3138/ptc.2015-24e
|View full text |Cite
|
Sign up to set email alerts
|

Interviewers' Experiences with Two Multiple Mini-Interview Scoring Methods Used for Admission to a Master of Physical Therapy Programme

Abstract: Purpose: To describe participants' attitudes, beliefs, and experiences with the use of two methods of scoring the Multiple Mini-Interview (MMI) for admission to a Master of Physical Therapy program: a rank-based scoring system (RBS; used from 2007 to 2013) and a criterion-based scoring system (CBS; tested in 2014). The MMI uses short independent assessments to obtain an aggregate score of candidates' professionalism and interpersonal skills, based on behavioural questions within scenarios that assess one attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Our online system provides for a fully automated interview as opposed to a human using videoconference technology to facilitate a human-assessed interview using MMI scenarios. Despite the concept of the automated interview being progressive, admissions staff saw substantial potential to mitigate subjectivity issues associated with human-led interviews through unintended bias and interviewer fatigue 22 . This was based on the consistency of the automated interview in contrast to the perceived nuanced differences between human interviewers conducting MMIs.…”
Section: Discussionmentioning
confidence: 99%
“…Our online system provides for a fully automated interview as opposed to a human using videoconference technology to facilitate a human-assessed interview using MMI scenarios. Despite the concept of the automated interview being progressive, admissions staff saw substantial potential to mitigate subjectivity issues associated with human-led interviews through unintended bias and interviewer fatigue 22 . This was based on the consistency of the automated interview in contrast to the perceived nuanced differences between human interviewers conducting MMIs.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple Mini Interviews (MMIs) are being increasingly used in the selection processes for students in a number of professions ( Christensen et al ., 2018 ; van der Spuy, Busch and Bidonde, 2016 ; Andrades et al ., 2014 ). They are used to assess a number of professional attributes including communication, empathy, decision making and taking responsibility ( Kelly et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, there has been an ongoing discourse about the merits of the personal or panel interview versus the multiple mini-interview (MMI). 25 In their article “Interviewers' Experiences with Two Multiple Mini-Interview Scoring Methods Used for Admission to a Master of Physical Therapy Programme,” van der Spuy and colleagues 1 explored the fairness and objectivity of two methods of scoring the MMI.…”
mentioning
confidence: 99%
“…The study by van der Spuy and colleagues 1 highlights the process that the University of Saskatchewan undertook to describe participants' attitudes, beliefs, and experiences using the rank-based and criterion-based methods of scoring. The results of their investigation revealed that the criterion-based scoring system was viewed more favourably by both interviewees and interviewers.…”
mentioning
confidence: 99%
See 1 more Smart Citation